2011
DOI: 10.1111/j.1460-2695.2011.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of PVD coatings on the tensile strength and low-cycle fatigue resistance of stainless steel and titanium alloys

Abstract: A B S T R A C T PVD coatings applied to components form hard, stronger layers and generate high residual compressive stresses that limit the plastic deformation in surface layers of the base metal thus increasing its tensile strength and resistance to fatigue loading. The purpose of this paper is to experimentally determine the influence of the deposition of 2 to 16.5-μm-thick PVD coatings of TiN , Cr, (Cr+TiN), (TiC)N, (TiAl)N onto specimens of stainless steel 321 and titanium alloys of types MILT-81556A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Figure 11 depicts the variation with strain of the stress and the instantaneous elastic modulus for the first and for the 5000th cycle of tests performed at 5 Hz, 0.025 mm mm À1 reference strain and 5000 cycles. It can be observed that a higher stress response (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) MPa, characteristic to the first cycle) corresponds to a lower stiffness (950-800 MPa) and vice versa, lower stress responses (0-15 MPa, characteristic to the 5000th cycle) exhibit higher stiffness (1030-930 MPa). Figure 12 presents the stress-strain and modulusstrain curves from a tensile test performed at 0.1 s À1 strain rate; value that is close to the strain rate resulted from tests performed at 5 Hz (0.075 s À1 ).…”
Section: Discussion Smentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 11 depicts the variation with strain of the stress and the instantaneous elastic modulus for the first and for the 5000th cycle of tests performed at 5 Hz, 0.025 mm mm À1 reference strain and 5000 cycles. It can be observed that a higher stress response (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) MPa, characteristic to the first cycle) corresponds to a lower stiffness (950-800 MPa) and vice versa, lower stress responses (0-15 MPa, characteristic to the 5000th cycle) exhibit higher stiffness (1030-930 MPa). Figure 12 presents the stress-strain and modulusstrain curves from a tensile test performed at 0.1 s À1 strain rate; value that is close to the strain rate resulted from tests performed at 5 Hz (0.075 s À1 ).…”
Section: Discussion Smentioning
confidence: 99%
“…19 Low-cycle fatigue (LCF) tests were developed for investigating the fatigue behaviour of metals at relative high strain/stress levels as a way to replicate the in-service loading patterns of some components. 20 The cycle strain/stress ratio R of LCF tests on metals can vary from negative values 21 to positive values, 22 and the tests are usually performed at low frequencies (<1 Hz). 22,23 The behaviour of fibre-reinforced composites is also investigated under LCF [24][25][26][27] and similarly, tests on polymers mostly demonstrate the Mullin's effect, and procedures rarely exceed 10 2 cycles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The residual stress is well known to be dependent on the coating layers organization and thickness, for example, the TiN hard coating 12 and Cu/W nanomultilayers 13 . The microstructure and mechanical properties of some layers in these multilayer coatings may change substantially with changing layer thickness across a thickness range, such as the electroplated Ni/Sn multilayered composites, 14 (Na 0.85 K 0.15 ) 0.5 Bi 0.5 TiO 3 multilayer thin films produced by spin coating 15 and multiple type of PVD coatings 16 . Multiple crack initiation mechanisms, including surface crack initiation and a series of different subsurface crack initiation mechanisms, may occur in the failure of multilayer coatings.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of thermal stresses which accompany the processes of production and operation of elements consisting of parts characterised by different mechanical and thermal properties, one must account for the possibility of internal stresses occurring in the element after its temperature has settled. This problem matters for numerous reasons, including those related to interfaces between ceramic and metallic materials [2][3][4][5][6]. Internal stresses combined with stresses triggered by thermal or mechanical loads may lead to destruction of an element.…”
Section: Introductionmentioning
confidence: 99%